Diversity and enzymatic activity of the microbiota isolated from compost based on restaurant waste and yard trimmings - da Silva Gaspar, Suelen; Assis, Lucas Lenin Resende de; Prado, Maria Paula Ramos do; Pedroso Miguel, Maria Gabriela; Magno dos Reis Ferreira, Gustavo; Schwan, Rosane Freitas; Pasqual, Moacir; Rigobelo, Everlon Cid; Castro, Rafael Peron; Buttrós, Victor Hugo; Dória, Joyce (Frontiers in Sustainable Food Systems, 2023)
The bad management of organic wastes negatively affects environmental quality and composting has been a viable recycling alternative. Microorganisms are responsible for waste degradation during the composting process and, consequently, for transforming this waste into natural fertilizer. This work aimed to analyze and identify the biodiversity of yeasts and filamentous fungi throughout a composting process based on organic residues under different treatments (commercial inoculum, non-commercial inoculum, and control treatment) and to investigate the enzymatic activity of these microorganisms. Microorganisms were isolated and identified from samples at 0, 5, 10, 20, 40, 60, and 120 days. Filamentous fungi were identified according to their macroscopic and microscopic characteristics, and yeasts were identified by sequencing the 18S rDNA region. All identified strains were evaluated for ligninolytic, cellulolytic, hemicellulolytic, amylolytic, pectinolytic, proteolytic, lipolytic, and ammonification. During the composting phases, the filamentous fungi were higher than the yeast population. At the beginning of the process, a higher number of species diversity was observed, and the population of yeasts and filamentous fungi was, on average, 6.50 log CFU g-1. The microbial communities were similar throughout the process in the two inoculated treatments, which showed more significant microbial activity, diversity, efficiency in the transformation of organic matter, and consequently, advantages in terms of the final product quality compared to the control treatment. The yeasts Pichia kudriavzevii, Pichia farinosa, Issatchenkia orientalis, and the filamentous fungi of the genus Aspergillus spp. proved to have high biotechnological value and could be used as starter cultures to accelerate the composting process.